Epistemic justification - Swinburne, Richard (Clarendon Press ; Oxford University Press, 2001)
Modern disputes about what makes a belief epistemically justified or rational are flawed through failing to recognize that there are different kinds of justifications that are in different ways indicative that the belief is true. I distinguish synchronic justification (the belief being a justified response to the believer's situation at the time) from diachronic justification (the belief constituting a justified response to adequate investigation over time); and, for each of these kinds, internalist justification (justification by introspectible factors) from externalist justification (justification by factors not necessarily accessible to the believer). A belief is internally synchronically justified if it is rendered inductively probable by the believer's basic beliefs; but 'inductively probable' may mean probable by true a priori standards (logically probable), by true standards to the best of the believer's ability to discover this (epistemically probable), or simply by the believer's own standards (subjectively probable). External synchronic justification is normally a matter of being produced by a reliable process, and there are many different ways of spelling that out. A belief is diachronically justified to the extent to which it results from adequate investigation. This depends (positively) on how probable it was that investigation would lead to evidence that would make a difference to the original probability of the belief; how probable it was that the issue was important; and (negatively) on how probable it was that investigation would cost much time and money. But all these 'probabilities' can be spelled out in different internalist and externalist ways. Almost all these kinds of justification are worth having, because it is logically probable that a belief justified in almost all these ways will be true. This account of justification is extended to give an account of different kinds of knowledge, all of which are worth having.